Digital tech infrastructure for e-waste manangment sector - Sanshodhan (ASCI Journal of Management)
Everyone is using godgets and domestic appliances in day to day life. The challenge arises once these products stop working, and responsible consumer, do not know where to dispose them of for sfe recycling. Unsafe disposal of goddess, electronics, and domestic appliances creates a lot of e-pollution, lading to air, water, and land pollution. Sanshodhan: an e-waste exchange provides digital infrastructure for prevention of such e-pollution, saving air, water and land from getting polluted. - Reproduced